Modulating Target Protein Biology Through the Re-mapping of Conformational Distributions Using Small Molecules - Lawson, Alastair D. G.; MacCoss, Malcolm; Baeten, Dominique L.; Macpherson, Alex; Shi, Jiye; Henry, Alistair J. (Frontiers in Chemistry, 2021)
Over the last ten years considerable progress has been made in the application of small molecules to modulating protein-protein interactions (PPIs), and the navigation from ‘undruggable’ to a host of candidate molecules in clinical trials has been well charted in recent, comprehensive reviews. Structure-based design has played an important role in this scientific journey, with three dimensional structures guiding medicinal chemistry efforts. However, the importance of two additional dimensions: movement and time is only now being realised, as increasing computing power, closely aligned with wet lab validation, is applied to the challenge. Protein dynamics are fundamental to biology and disease, and application to PPI drug discovery has massively widened the scope for new chemical entities to influence function from allosteric, and previously unreported, sites. In this forward-looking perspective we highlight exciting, new opportunities for small molecules to modulate disease biology, by adjusting the frequency profile of natural conformational sampling, through the stabilisation of clinically desired conformers of target proteins.